2018
DOI: 10.1016/j.molcel.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Functions of FACT in Breaking the Nucleosome and Maintaining Its Integrity at the Single-Nucleosome Level

Abstract: The human FACT (facilitates chromatin transcription) complex, composed of two subunits SPT16 (Suppressor of Ty 16) and SSRP1 (Structure-specific recognition protein-1), plays essential roles in nucleosome remodeling. However, the molecular mechanism of FACT reorganizing the nucleosome still remains elusive. In this study, we demonstrate that FACT displays dual functions in destabilizing the nucleosome and maintaining the original histones and nucleosome integrity at the single-nucleosome level. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 59 publications
(94 reference statements)
13
87
0
1
Order By: Relevance
“…Its translocation across the membrane, if allowed, would release energy of 10 kJ/mol (or ~4RT; assuming ΔpH = 0). This level of force is considered large for a MP floating in the lipid bilayer, and is comparable to those observed in typical molecular events within the cell . Interestingly, the electrostatic force of the ΔΨ exerted on negatively charged residues in a nascent polypeptide chain traversing the Escherichia coli inner membrane has been detected experimentally .…”
Section: The Electrostatic Force Originating From the Charge Gradientmentioning
confidence: 71%
See 1 more Smart Citation
“…Its translocation across the membrane, if allowed, would release energy of 10 kJ/mol (or ~4RT; assuming ΔpH = 0). This level of force is considered large for a MP floating in the lipid bilayer, and is comparable to those observed in typical molecular events within the cell . Interestingly, the electrostatic force of the ΔΨ exerted on negatively charged residues in a nascent polypeptide chain traversing the Escherichia coli inner membrane has been detected experimentally .…”
Section: The Electrostatic Force Originating From the Charge Gradientmentioning
confidence: 71%
“…This level of force is considered large for a MP floating in the lipid bilayer, and is comparable to those observed in typical molecular events within the Zhang and Li cell. [17][18][19][20] Interestingly, the electrostatic force of the ΔΨ exerted on negatively charged residues in a nascent polypeptide chain traversing the Escherichia coli inner membrane has been detected experimentally. 21 Therefore, it is highly probable that both the conformation and function of a charge-carrying MP are strongly influenced by the existence and/or change of ΔΨ, provided that the protein is able to move relative to E Ψ .…”
mentioning
confidence: 99%
“…For instance, FACT may bind to the nucleosome and remove one histone dimer ahead of the Pol II and reassemble the nucleosome after Pol II traversal. 3638 . These early regulatory steps as Pol II invades the nucleosome not only gate gene expression but also permit the regulation of chromatin integrity and of epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…The structural changes that occur in canonical nucleosomes upon FACT binding are likely key to addressing this question, as the observed stimulation is specific to nucleosomal substrates. FACT can reorganize the nucleosome by disrupting histone/DNA contacts, leaving the nucleosome in an "open" or "destabilized" state (Chen et al, 2018;Kemble et al, 2015;McCullough et al, 2011) and by fully displacing H2A/H2B heterodimers (Belotserkovskaya et al, 2003;Chen et al, 2018;Hsieh et al, 2013;Orphanides et al, 1999;Wang et al, 2018;Xin et al, 2009a). The most straightforward explanation for the effect of FACT on Ubp10 activity is that FACT increases H2B deubiquitination by evicting H2A/H2B-Ub heterodimers, which are an excellent substrate for Ubp10 (Figures 2A and 3C).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the observed stimulatory effect of FACT is that it alters nucleosomal structure, making it a better substrate for Ubp10. Previous studies have shown that FACT binding can destabilize the canonical nucleosomes, disrupting the octamer/DNA contacts, which could result in displacement of H2A/H2B heterodimers (Belotserkovskaya et al, 2003;Chen et al, 2018;McCullough et al, 2011), thereby providing better substrates for Ubp10 ( Figure 2). During nucleosome reorganization induced by FACT, surfaces of H2A/H2B heterodimers that are buried in the context of the nucleosome become more accessible (Kemble et al, 2015) even while the components remained tethered together Xin et al, 2009a;Yang et al, 2018), which could enhance accessibility of H2B-Ub for deubiquitination by Ubp10 even without dimer eviction.…”
Section: Fact Stimulates Ubp10 Dub Activity On Nucleosomesmentioning
confidence: 97%